Vector-based analysis of cortical activity associated with dumbbell exercise using functional near-infrared spectroscopy - Kato, Toshinori (Frontiers in Sports and Active Living, 2022)
The mechanisms via which the brain and muscles work together remain poorly understood. The use of vector-based fNIRS, to propose a new metric and imaging method to understand neural activation during dumbbell-lifting exercises. This method can simultaneously measure oxyhemoglobin (oxyHb) and deoxyHb levels so that the angle k: Arctan (deoxyHb/oxyHb) represents the degree of oxygen exchange in the brain and can be used to quantify the distribution of oxygen consumption. The amplitude L of the vector reflects the intensity of the response caused by the amount of change in Hb. This study used vector-based fNIRS to simultaneously measure the left primary motor cortex (left M1), multiple peripheral regions, and the right biceps brachii muscle. The subjects were seven healthy adults. The task was a dumbbell-lifting exercise involving flexion and extension of the elbow joints of both arms. Dumbbell weights of 0 (no dumbbell), 4.5, and 9.5 kg were used. During dumbbell exercise, oxygen exchange increased in the left M1, indicating increased local oxygen consumption. Around the left M1, the cerebral oxygen exchange decreased, and oxygen supply increased without cerebral oxygen consumption. The spatial agreement between the maximum value of oxygen exchange k and L during the task was <20%. Therefore, the dumbbell-lifting exercise task study reported here supported the hypothesis that cerebral oxygen consumption associated with neural activation does not coincide with the distribution of cerebral oxygen supply. The relationship between the brain oxygen supply from the site of increased oxygen exchange in the brain and its surrounding areas can be quantified using the vector method fNIRS.